1991
DOI: 10.1177/001872089103300402
|View full text |Cite
|
Sign up to set email alerts
|

Aurally Aided Visual Search in the Central Visual Field: Effects of Visual Load and Visual Enhancement of the Target

Abstract: Visual search performance was examined in a two-alternative, forced-choice paradigm. The task involved locating and identifying which of two visual targets was present on a trial. The location of the targets varied relative to the subject's initial fixation point from 0 to 14.8 deg. The visual targets were either presented concurrently with a sound located at the same position as the visual target or were presented in silence. Both the number of distractor visual figures (0-63) present in the field during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
58
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 2 publications
11
58
2
Order By: Relevance
“…1 The present study was designed to replicate and extend Van der Burg et al's (2008) findings using the auditory-visual pip-and-pop and vibrotactile-visual poke-and-pop paradigms to explore how visual search performance is modulated by cues that were not only temporally synchronous (presented in synchrony with the color change of the visual target) but also spatially informative with regard to the likely location of the target (in the left or right hemifield). The benefits of having auditory or tactile cues that are either temporally synchronous (e.g., Chan & Chan, 2006;Dalton & Spence, 2007;Van der Burg et al, 2008Vroomen & de Gelder, 2000) or spatially informative (Ho, Santangelo, & Spence, 2009;Ho, Tan, & Spence, 2006;Perrott et al, 1996;Perrott et al, 1991) have been repeatedly demonstrated trade-offs (see Spence, Kingstone, Shore, & Gazzaniga, 2001;Townsend & Ashby, 1983). IE scores were calculated by dividing each participant's mean RT for each condition by their proportion of correct responses for that condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The present study was designed to replicate and extend Van der Burg et al's (2008) findings using the auditory-visual pip-and-pop and vibrotactile-visual poke-and-pop paradigms to explore how visual search performance is modulated by cues that were not only temporally synchronous (presented in synchrony with the color change of the visual target) but also spatially informative with regard to the likely location of the target (in the left or right hemifield). The benefits of having auditory or tactile cues that are either temporally synchronous (e.g., Chan & Chan, 2006;Dalton & Spence, 2007;Van der Burg et al, 2008Vroomen & de Gelder, 2000) or spatially informative (Ho, Santangelo, & Spence, 2009;Ho, Tan, & Spence, 2006;Perrott et al, 1996;Perrott et al, 1991) have been repeatedly demonstrated trade-offs (see Spence, Kingstone, Shore, & Gazzaniga, 2001;Townsend & Ashby, 1983). IE scores were calculated by dividing each participant's mean RT for each condition by their proportion of correct responses for that condition.…”
Section: Methodsmentioning
confidence: 99%
“…The presentation of spatially informative nonvisual cues-specifically, auditory cues that are colocalized with visual targets-has been shown to reduce visual search latencies by several thousand milliseconds for peripherally located visual targets (i.e., for targets presented at eccentricities exceeding 90º from central fixation; see, e.g., Perrott, Cisneros, McKinley, & D'Angelo, 1996;Perrott, Saberi, Brown, & Strybel, 1990;Perrot, Sadralodabai, Saberi, & Strybel, 1991). The p presentation of spatially uninformative auditory cues has also been shown to reduce visual search latencies for vin sual targets presented in the central field by more than 200 msec (e.g., Dufour, 1999;Perrott et al, 1996;Perrott et al, 1991).…”
mentioning
confidence: 99%
“…In one experiment (Perrott et al, 1991) Perrott et al (1996) investigated the trivial case (i.e., one target, zero distractors) of an aurally aided visual search task in which the visual field was less restricted. In this study the target was presented on the interior surface of a geodesic sphere to an observer seated at the center.…”
Section: Introductionmentioning
confidence: 99%
“…However, searching for and finding visual information within a 30-degree FOV might prove to be difficult, especially when there is a large number of visual objects on the display. Perrott, Sadralodabai, Saberi, and Strybel (1991) found that response time for target identification without audio cues doubled from 700 ms to 1400 ms when the number of visual objects increased from 2 to 64. Visual search may be very difficult in situations when visual targets include revisions of an already complex display, such as the change of military symbols on a map already populated by a large number of military symbols.…”
Section: Introductionmentioning
confidence: 98%
“…Providing spatial auditory cues as guides (also known as aurally guided visual search) can facilitate detection of a visual target (Perrott et al 1991;Elias, 1995Elias, , 1996Perrott, Cisneros, McKinley, & D'Angelo, 1995, 1996Strybel, Boucher, Fujawa, & Volp, 1995;Fujawa & Strybel, 1997). Begault (1993) found that visual search times of commercial pilots were reduced by several (2.2) seconds when spatially correlated sounds were present.…”
Section: Introductionmentioning
confidence: 99%